A modernização administrativa no processo de expansão universitária por meio do Reuni: estudo de caso na Faculdade de Medicina da UFC - Severino, Lis Soares (2022)
The main subject of this study is the university expansion implemented through the Program for Support to Plans of Restructuring and Expansion of Federal Universities (REUNI), with the objective of improving the quality of the university education. It aimed to focus on the transition from the management model of the Universidade Federal do Ceará (UFC), according to the guidelines of the Administrative Reform of the Brazilian State, drafted by the Government of Fernando Henrique Cardoso (FHC) (1995-2002), which had the purpose of administrative modernization of the State, replacing the bureaucratic management of public agencies with the model of empowerment management.It was assumed that the transition process in UFC was boosted with the funding for restructuring and expanding public universities of REUNI, which was a public policy implemented in the Government of Luis Inácio Lula da Silva (Lula) (2003-2010), the successor of Government FHC.The main objective was describing, comprehending, and evaluating the contribution of REUNI to the administrative modernization of UFC in the perception of technical-administrative personnel involved in that process as their daily work. This study is exploratory and descriptive, intending to gather both quantitative and qualitative aspects that compose the object of study, based on the model of evaluation of experiential public policies. The results reveal the effective acquisition of some components of the Administrative Reform in the after-REUNI university environment, with improvement of indicators in the administrative process. It was detected involution in the bureaucratic-patrimonialist culture; objective criteriums were defined for acts towards administration interests; delivery of services became more professional;behavior was favored for ethical, rational, and respectful to public property; increased hiring based on public contest; incentive to capacity building; better qualification and valorization of technical workers; improvement of the quality and dynamics of social returns; increased investment in infrastructure; renewal of technological equipment; adequacy of administrative and teaching environments; administrative processes were revised, updated, and standardized; labor routines were digitalized; and institutional communication was improved.